Clinical and imaging progression over 10 years in a patient with primary progressive apraxia of speech and autopsy-confirmed corticobasal degeneration. Issue 2 (4th March 2018) - Tetzloff, Katerina A.; Duffy, Joseph R.; Strand, Edythe A.; Machulda, Mary M.; Boland, Sarah M.; Utianski, Rene L.; Botha, Hugo; Senjem, Matthew L.; Schwarz, Christopher G.; Josephs, Keith A.; Whitwell, Jennifer L.
ABSTRACT: Primary progressive apraxia of speech (PPAOS) is a neurodegenerative disorder in which AOS is the sole presenting complaint. We report clinical and neuroimaging data spanning 10 years from disease onset-to-death in a 49 year-old male PPAOS patient, DY, who died with corticobasal degeneration. He presented with AOS with normal neuroimaging. Abnormalities in the caudate nucleus, supplementary motor area, cingulate, insula, and Broca's area were observed after five years, with involvement of motor cortex and development of agrammatism, Parkinsonism, and dysarthria three years later. Cognitive impairment and temporoparietal atrophy were late features. This data provides important insight into disease progression of corticobasal degeneration when presenting as PPAOS.